Impact of the MLC on the MRI field distortion of a prototype MRI‐linac. Issue 12 (8th November 2013) - Kolling, Stefan; Oborn, Brad; Keall, Paul
Abstract : Purpose: : To cope with intrafraction tumor motion, integrated MRI‐linac systems for real‐time image guidance are currently under development. The multileaf collimator (MLC) is a key component in every state‐of‐the‐art radiotherapy treatment system, allowing for accurate field shaping and tumor tracking. This work quantifies the magnetic impact of a widely used MLC on the MRI field homogeneity for such a modality. Methods: : The finite element method was employed to model a MRI‐linac assembly comprised of a 1.0 T split‐bore MRI magnet and the key ferromagnetic components of a Varian Millennium 120 MLC, namely, the leaves and motors. Full 3D magnetic field maps of the system were generated. From these field maps, the peak‐to‐peak distortion within the MRI imaging volume was evaluated over a 30 c m diameter sphere volume (DSV) around the isocenter and compared to a maximum preshim inhomogeneity of 300 μ T . Five parametric studies were performed: (1) The source‐to‐isocenter distance (SID) was varied from 100 to 200 c m, to span the range of a compact system to that with lower magnetic coupling. (2) The MLC model was changed from leaves only to leaves with motors, to determine the contribution to the total distortion caused by MLC leaves and motors separately. (3) The system was configured in the inline or perpendicular orientation, i.e., the linac treatment beam was oriented parallel or perpendicular to the magnetic field direction. (4) The treatment field size was varied from 0 × 0 to 20 × 20 c m 2, to span the range of clinical treatment fields. (5) The coil currents were scaled linearly to produce magnetic field strengths B 0 of 0.5, 1.0, and 1.5 T, to estimate how the MLC impact changes with B 0 . Results: : (1) The MLC‐induced MRI field distortion fell continuously with increasing SID. (2) MLC leaves and motors were found to contribute to the distortion in approximately equal measure. (3) Due to faster falloff of the fringe field, the field distortion was generally smaller in the perpendicular beam orientation. The peak‐to‐peak DSV distortion was below 300 μ T at S I D ≥ 130 c m (perpendicular) and S I D ≥ 140 c m (inline) for the 1.0 T design. (4) The simulation of different treatment fields was identified to cause dynamic changes in the field distribution. However, the estimated residual distortion was below 1.2 m m geometric distortion at S I D ≥ 120 c m (perpendicular) and S I D ≥ 130 c m (inline) for a 10 m T / m frequency‐encoding gradient. (5) Due to magnetic saturation of the MLC materials, the field distortion remained constant at B 0 > 1.0 T . Conclusions: : This work shows that the MRI field distortions caused by the MLC cannot be ignored and must be thoroughly investigated for any MRI‐linac system. The numeric distortion values obtained for our 1.0 T magnet may vary for other magnet designs with substantially different fringe fields, however the concept of modest increases in the SID to reduce the distortion to a shimmable level is generally applicable.